2020
DOI: 10.1039/d0an01273d
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic monitoring of a bi-enzymatic reaction at a single biomimetic giant vesicle

Abstract: Giant unilamellar vesicles were used as individual biomimetic micro-reactors wherein a model bi-enzymatic reaction involving a glucose oxidase (GOx) and the horseradish peroxidase (HRP) was monitored by confocal microscopy. These...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…We assume that the flux detected at one location of the membrane is representative of the mean flux produced by the GUV. The hypothesis is reinforced by our recent results with the same type of enzymatic GUVs analyzed by fluorescence confocal microscopy . The Amplex Red assay was used to image the bienzymatic system composed of GOx and horseradish peroxidase (HRP); we observed that resorufin, the end-product of the reactions, was emitted over the whole surface of the GUV, meaning that the composition within the GUV volume was homogeneous at the timescale of the experiment.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…We assume that the flux detected at one location of the membrane is representative of the mean flux produced by the GUV. The hypothesis is reinforced by our recent results with the same type of enzymatic GUVs analyzed by fluorescence confocal microscopy . The Amplex Red assay was used to image the bienzymatic system composed of GOx and horseradish peroxidase (HRP); we observed that resorufin, the end-product of the reactions, was emitted over the whole surface of the GUV, meaning that the composition within the GUV volume was homogeneous at the timescale of the experiment.…”
Section: Resultsmentioning
confidence: 77%
“…The enzymatic reaction in single GUVs was induced by microinjections of low quantities of glucose oxidase (GOx from Aspergillus Niger). In a recent study, 73 we have defined the experimental conditions allowing a kinetic and quantitative control of the GOx activity in the same GUVs as used herein. A hydrogen peroxide fluorescent assay (Amplex Red fluorogenic probe and peroxidase enzyme) revealed by laser scanning confocal microscopy on the GUVs that such liposomes allow a passive diffusion of glucose and resorufin (fluorescent reporter of the Amplex Red assay).…”
Section: Performing the Gox Catalysis In A Single Guv And Detecting T...mentioning
confidence: 99%
“…The cascade reaction was mediated by two enzymes: glucose oxidase (GOx) and horseradish peroxidase (HRP), which work in tandem to oxidize a fluorogenic probe (Amplex TM Red). [43] The bioreactors were created by encapsulation of the GOx and HRP in giant polymer vesicles using the SDE method. The reaction was started by addition of Amplex TM Red into the medium surrounding the bioreactors to a final concentration of 30 µM.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Lobovkina’s group reported that by applying positive pressure toward the inside of the GUV at the contact tip of a micropipette, a string-bead structure made of a stretched GV membrane was produced inside the GUV [ 81 ]. In addition, microinjection is also possible with a micropipette by piercing a part of the GV membrane with a tip with a diameter of 1 μm [ 82 , 83 , 84 ].…”
Section: Manipulation Methods Of Gvsmentioning
confidence: 99%